A Cuban Refugee's Journey to the American Dream : The Power of Education - Gonzalez, Gerardo M. (Book collections on Project MUSE., 2018)
In this deeply moving memoir, González recounts his remarkable journey from Cuba and his upward track through education in United States. At a time when the fates of millions of refugees and Hispanics in the United States has never been more uncertain, González's story is more important than ever.